Uranium beam characterization at CIRCE for background and contamination determinations. (September 2015) - De Cesare, M.; De Cesare, N.; D'Onofrio, A.; Fifield, L.K.; Gialanella, L.; Terrasi, F.
Abstract: The Accelerator Mass Spectrometry (AMS) is the most sensitive technique, compared either to the Inductively Coupled Plasma (ICP-MS) or Thermal Ionization (TI-MS) mass spectrometer, for the actinide (e.g. 236 U, x Pu isotopes) measurements. They are present in environmental samples at the ultra trace level since atmospheric tests of Nuclear Weapons (NWs) performed in the past, deliberate dumping of nuclear waste, nuclear fuel reprocessing, on a large scale, and operation of Nuclear Power Plants (NPPs), on a small scale, have led to the release of a wide range of radioactive nuclides in the environment. At the Center for Isotopic Research on Cultural and Environmental heritage (CIRCE) in Caserta, Italy, an upgraded actinide AMS system, based on a 3-MV pelletron tandem accelerator, has been developed and routinely operated. At CIRCE a charge state distribution as a function of terminal voltage, the beam emittance, measured in the 20° actinides dedicated beam line, as well as the energy and position validation of the U ions were performed in order to determine the best measurement conditions. A 236 U/ 238 U isotopic ratio background level of about 5×10 −12 or 3×10 −13, depending on the Time of Flight-Energy (TOF-E) configurations, as well as the spatial distribution of the 235 U, 238 U interferences ions and a 236 U contamination mass of about 0.5 fg have been determined.